Dwarf shrub hydraulics: two Vaccinium species (Vaccinium myrtillus, Vaccinium vitis‐idaea) of the European Alps compared. Issue 4 (4th March 2015) - Ganthaler, Andrea; Mayr, Stefan
Abstract : Vaccinium myrtillus and Vaccinium vitis‐idaea are two dwarf shrubs widespread in the European Alps. We studied the hydraulics of these species hypothesizing that (1) the hydraulic architecture of dwarf shrubs differs from trees, (2) hydraulic properties reflect the species' ecological amplitude and (3) hydraulic properties vary spatially and seasonally. Key hydraulic parameters (osmotic potential, turgor loss point, xylem hydraulic conductivity, vulnerability to drought‐induced embolism, stomata closure, drought‐induced cell damage and embolism repair) and related wood anatomical traits (conduit diameter and conduit wall reinforcement) were analyzed at four sites in Tyrol, Austria. Both species exhibited low hydraulic safety as well as low hydraulic efficiency. Fifty percentage embolism accumulated at −2.08 ( V. myrtillus ) and −1.97 MPa ( V. vitis‐idaea ), 88% stomata closure was at −2.19 and −2.35 MPa, respectively. After drought, both species showed embolism repair on re‐watering. Site‐specific variation within species was low, while seasonal changes in embolism resistance and turgor loss point were observed. Results indicate that studied Vaccinium species have a high risk for embolism formation. This is balanced by refilling capacities, which are probably based on the small growth height of dwarf shrubs. V. vitis‐idaea, which occurs on drier sites, showed more efficient repair and a lower turgor loss point than V. myrtillus .